Challenges and Opportunities for QRIS Implementation as a Digital Payment System in Indonesia - Rachman, Abdul; Julianti, Niken; Arkoyah, Siti (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2024)
This research aims to analyze the challenges and opportunities for implementing QRIS (Quick Response Code Indonesian Standard) as one of the digital payment systems in Indonesia which has been provided by Bank Indonesia as an application that provides convenience, speed, and efficiency in payment transactions. However, the implementation of QRIS as a digital payment system in Indonesia still faces many challenges, such as limited internet access, competition with other payment systems, security aspects in use that have the potential for fraud or data theft, and low public understanding of QRIS. This research uses descriptive qualitative research methods with a focus on challenges and opportunities in implementing QRIS in Indonesia. The primary data sources in this research are observations and in-depth interviews with business actors who use QRIS. Secondary data sources were obtained from Bank Indonesia QRIS documents and data. This research found that the challenges in implementing QRIS in Indonesia are still low support from the central government and regional governments in accelerating the use of QRIS, not yet optimal cooperation between financial institutions, industry, and society, inadequate information technology infrastructure, and low public understanding about QRIS. Meanwhile, QRIS has enormous opportunities because it is one of the instruments in encouraging digital economic acceleration that is inclusive and efficient. QRIS has huge market potential because there is an increasing number of smartphone users every year.